Cities, Immigrants and Political Participation: The case of Constituencies in Milan - Colloca, Carlo; Lipari, Licia; Lombardo, Elisa (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
The essay proposes an empirical study on the “territorialization” of social inequalities in Italian cities carried out with the support of digital cartography tools (Geographic Information System). The essay collects some of the results of the research project, still in progress, "GRIDAVI - Risk Management, Decision Uncertainty and Social Vulnerability", funded by the University of Catania as part of the PIACERI research program (PIAno di inCEntivi per la RIcerca di Ateneo 2020-22), Line of action 2.